12x-5=6x

Simple and best practice solution for 12x-5=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-5=6x equation:



12x-5=6x
We move all terms to the left:
12x-5-(6x)=0
We add all the numbers together, and all the variables
6x-5=0
We move all terms containing x to the left, all other terms to the right
6x=5
x=5/6
x=5/6

See similar equations:

| m+22=43 | | 6n-2=(n-3 | | 45=-5h | | 5b–11=2 | | -3(x-4)+5x=10 | | 2n-10=-4 | | -(10-x)=7 | | 6(4n+3)=-174 | | 17-61=25-3r | | 4/3x−5/6=52 | | -8x+6(x+8=38 | | 17a-33=1 | | 5-6(a+12)=7+a | | 14/x+6=7/4 | | 9+g=-17 | | 3k-2k=2k-5-4K | | 6+4x=-x+6 | | –11=24+–5v | | (1/3)-x=(-1/2) | | 3x+2=4x–93.5x–8= | | v-4.6=98 | | 91=7(m+5) | | 48000=1/2m•20^2 | | 1.4–0.04x=5.20 | | 3q−=8 | | 4x+3-2x=8+2x | | |3x-4|-3=11 | | 3q−1=8 | | -10+7x=-30+3x | | y(8)=-192 | | 6x+1=5x+42.3x+4= | | 3(x–4)+4x=16 |

Equations solver categories